Service quality in baggage handling: The case of Malaysia Airlines / Nazatulzarit Kamesan - Kamesan, Nazatulzarit (Faculty of Business and Management, 2007)
The purpose of this research is to study the identify the problems of baggage handling by Malaysia Airlines especially in terms of service quality and to examine the relationship between Service Quality and Baggage Handling Service Satisfaction . Moreover, this study is to identify the level of customer satisfaction in relation to service quality in baggage handling. It is believed that the attributes offered will determine whether the customers have a good or poor expectation towards Malaysia Airlines baggage handling. The findings showed that the gaps between Consumer Expectation and Perceived are wide. The researcher is also identifying that the reliability, tangibles and assurance of the service quality are not influenced by Baggage Handling Service Satisfaction . The results also showed most of the respondents were agree with the service quality and moderate in their satisfaction. In this study, researcher used primary data, quantitative research and non comparative scales for data collection. Based on reliability test, frequency analysis and cross tabulation analysis, a clear findings and result is observed.